STRATEGI KOMUNIKASI UNTUK MEMPROMOSIKAN DAN MENINGKATKAN POTENSI LOKAL WISATA PULAU BAWEAN - Satvikadewi, A.A.I. Prihandari; Hamim, Hamim (representamen, 2018)
This study discusses how the communication strategies carried out in the Bawean Island tourism suprastructure to promote the local tourism potential of Bawean Island and the use of the media to promote the local tourism potential. The suprastructure elements include ideas, thoughts, people's philosophy of life manifested in rules, institutions and attitudes the daily lives of the Bawean people in addressing the development of tourism in their area. This study employs 9 aspects of tourism communication refering to Bungin (2016). Of the eleven local tourism objects studied, as well as in-depth interviews with the Gresik Regency Tourism Official, it was found that there were communication gaps in promotional activities and the use of media to communicate the local tourism potential of Bawean Island mainly due to a lack of common understanding of tourism communication strategy. This gap resulted in not only the decline in the number of visitors to Bawean Island in some particular destination, but also worsen the local tourism potential of Bawean Island, especially in some basic facilities such as tourism information and cleanliness of tourist destination area, as well as the lack of development of the creative industry as a carrying capacity of tourism communication.Keywords: tourism communications, local potential, Bawean